Eulerian network modeling of longitudinal dispersion. Issue 10 (29th October 2015) - Mehmani, Yashar; Balhoff, Matthew T.
Abstract: A novel Eulerian network model that incorporates "shear dispersion, " the stretching of solute due to nonuniform velocity profiles within pore throats is developed. The superposing transport method (STM) is nonlocal in time (i.e., uses information from several previous time steps) and is equivalent to performing network‐wide time convolutions of elementary throat response functions. Predicted macroscopic longitudinal dispersion coefficients for disordered sphere packs are in good agreement with published experimental data. We further investigate the impact of mixing assumptions within pores on macroscopic longitudinal dispersion and find the dependence to be weak for disordered sphere packs. Limitations of Eulerian network models as a whole are also discussed, and their inappropriateness for ordered porous media concluded. Key Points: Novel nonlocal Eulerian network model developed for solute transport Model accounts for nonuniform velocity profiles within pore throats Predicted longitudinal dispersion coefficients agree with experiments